Scour analysis downstream a converging stepped spillway equipped with a jump bucket - N. Figueiredo (2014)
The present work is related to the experimental study of the energy dissipation downstream of a converging stepped spillway equipped downstream with a ski jump bucket. The experiments were carried out with a movable stilling basin bed which allowed the scour hole characterization. Obtained results were compared with expressions from the literature review allowing the determination of the one that presented the most accurate prediction.